2018
DOI: 10.1155/2018/1647923
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Simple High Performance Liquid Chromatography/UV Method for Simultaneous Determination of Urinary Uric Acid, Hypoxanthine, and Creatinine in Human Urine

Abstract: Uric acid and hypoxanthine are produced in the catabolism of purine. Abnormal urinary levels of these products are associated with many diseases and therefore it is necessary to have a simple and rapid method to detect them. Hence, we report a simple reverse phase high performance liquid chromatography (HPLC/UV) technique, developed and validated for simultaneous analysis of uric acid, hypoxanthine, and creatinine in human urine. Urine was diluted appropriately and eluted with C-18 column 100 mm × 4.6 mm with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 19 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…The UOD oxidizes uric acid (UA) to allantoin and has been used therapeutically for the prevention and treatment of hyperuricemia. [ 42 ] By measuring the specific absorbance of UA at 293 nm, [ 43 ] we observed that pero ‐nanozysome effectively degraded UA in vitro. With the UA as the substrate, the pero ‐nanozysome showed almost fivefold higher degradation rate for UA compared with N ‐nanozyme (Figure S5a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The UOD oxidizes uric acid (UA) to allantoin and has been used therapeutically for the prevention and treatment of hyperuricemia. [ 42 ] By measuring the specific absorbance of UA at 293 nm, [ 43 ] we observed that pero ‐nanozysome effectively degraded UA in vitro. With the UA as the substrate, the pero ‐nanozysome showed almost fivefold higher degradation rate for UA compared with N ‐nanozyme (Figure S5a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the reported LOD and LOQ for AA using HPLC were 1.2 × 10 −3 g/L and 3.4 × 10 −3 g/L, respectively [ 38 ]. Furthermore, the reported LOD and LOQ for UA using HPLC were 0.30 μg/mL and 0.89 μg/mL, respectively [ 39 ]. Therefore, the electroanalytical methods presented in this work are competitive with HPLC for the analysis of EP, AA, and UA in terms of LOD and LOQ.…”
Section: Resultsmentioning
confidence: 99%
“…In a healthy body system, UA concentration ranges from 0.1‐4 mM and 1.5‐4.4 mM in blood and urine respectively . Elevated concentration of UA in human body has been implicated with diseases like gout, Lesch‐Nyan disease, obesity, diabetes, heart diseases and kidney‐related diseases . Hence, its prompt detection and monitoring is vital for human health protection.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical procedures have been developed for detection of uric acid in the past. These include isotopic dilution mass spectroscopy and liquid chromatography, chemiluminescence and electrochemical biosensors . etc.…”
Section: Introductionmentioning
confidence: 99%